Optimizing Gear Ratios for Vehicle Performance Enhancement Using Taguchi Method - Shaiful Fadzil Zainal Abidin; Mohamad Helmi Ripin; Rifqi Irzuan Abdul Jalal; Nurulafiqah Aziz (Journal of Advanced Industrial Technology and Application, 2024)
Gear ratio is a term used to describe the relationship between the number of teeth on two interlocking gears. It determines the speed and torque of a mechanical system, with higher gear ratios providing more torque but lower speed, while lower ratios offer higher speed but less torque. The study aims to design and develop a 1D vehicle physics model for powertrain matching and fuel economy prediction with the car's performance. For this study, the vehicle is modeled in GT-Suite to predict vehicle performance and fuel economy. The baseline results are compared with the actual testing data with the correlation of each parameter, performance, and fuel economy, which resulted in less than a 3% tolerance difference. The Taguchi method determines the optimal selection of gear ratios, while each gear ratio's significance toward the complete transmission set is calculated using ANOVA. The test subject for this research study is the Proton Saga 1.3L VVT, equipped with a 4-speed automatic transmission. The simulation results show an improvement of 3.36% for standing start acceleration and 3.18% for MDC fuel economy compared to the baseline model. Combining a 1D simulation cycle and statistical analysis approaches is a promising solution for optimizing system performance and fuel economy.